Toll-Like Receptor-2 and-4 Expression by Maternal Neutrophils in Preterm Labor - Moco, Natalia Prearo [UNESP] (2018)
Background and Aims: The inflammatory response in preterm parturition is regulated by the innate immune system. Toll-like receptors (TLR)-2 and TLR-4 are innate immune receptors that recognize the microorganisms most frequently involved in amniotic cavity infections, which are associated with activating the inflammatory response at the maternal-fetal interface during preterm labor. This study aimed to evaluate the expression of TLR-2 and TLR-4 in maternal neutrophils in preterm labor. Methods: A cross-sectional study was conducted in the Obstetrics Care Unit of Botucatu Medical School, UNESP, Brazil. The preterm group was composed of 20 pregnant women who presented preterm labor and preterm delivery. The control group was composed of 20 nonlaboring pregnant women matched to the preterm group by gestational age. Neutrophils were isolated from peripheral blood and TLR expressions were performed by real-time polymerase chain reaction and flow cytometry. Results: Gene expressions of TLR-2 and TLR-4 in neutrophils from the preterm group were statistically higher than expressions in neutrophils from the matched control group. The percentage of TLR-4(+) neutrophils was higher in the preterm group than the matched control group, while the percentage of TLR-2(+) neutrophils did not differ between groups. Conclusion: TLR-4 expression in maternal neutrophils is associated with spontaneous preterm labor. (C) 2017 S. Karger AG, Basel